A new gold-colored Lepanthes (Pleurothallidinae: Orchidaceae) from Southeast Ecuador - Baquero, Luis E. (2020)
Lepanthes vere-aurum, a new species of the orchid subtribe Pleurothallidinae, discovered in Zamora Chinchipe province, southeast Ecuador, is described here. We compare L. vere-aurum to L. brenneri, the only similar species, from which it differs in having larger leaves and longer inflorescences. Also, L. vere-aurum has an obovate, concave, long-acuminate dorsal sepal and a concave appendix with a pubescent crest underneath and with a long, pubescent apex,versus a flat, triangular-ovate, acuminate dorsal sepal and a smaller appendix with a ciliate apex in L. brenneri. Some information about its phenology and ecology is additionally provided. Key Words: Cordillera del Cóndor, endangered orchid, Epidendroideae, Lepanthes brenneri, new orchid species